2013
DOI: 10.3109/08916934.2012.750302
|View full text |Cite
|
Sign up to set email alerts
|

During apoptosis HMGB1 is translocated into apoptotic cell-derived membraneous vesicles

Abstract: High mobility group box protein B1 (HMGB1), a nuclear protein reportedly involved in the structural organisation of DNA, is released from necrotic cells or upon cellular activation. After its release into the extracellular space, HMGB1 serves as a mediator of inflammation. In contrast to necrotic cells, apoptotic ones usually do not release HMGB1. Formation and release of membranous vesicles is a well-known feature of apoptotic cell death. Only recently, subcellular membrane vesicles, such as those released du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Data from our prior publications (11, 26, 44) as well as those from other investigators (45, 46)strongly indicates that the release of HMGB1 from the intestinal epithelium after TLR4 activation requires enterocyte apoptosis, that enterocyte apoptosis is induced by the activation of TLR4, and that the mechanisms leading to enterocyte apoptosis require the induction of endoplasmic reticulum stress on the enterocytes. Specifically, we have shown that TLR4 activation on the intestinal epithelium leads to the induction of ER stress within the intestinal epithelium which leads to enterocyte apoptosis (11).…”
Section: Discussionmentioning
confidence: 53%
“…Data from our prior publications (11, 26, 44) as well as those from other investigators (45, 46)strongly indicates that the release of HMGB1 from the intestinal epithelium after TLR4 activation requires enterocyte apoptosis, that enterocyte apoptosis is induced by the activation of TLR4, and that the mechanisms leading to enterocyte apoptosis require the induction of endoplasmic reticulum stress on the enterocytes. Specifically, we have shown that TLR4 activation on the intestinal epithelium leads to the induction of ER stress within the intestinal epithelium which leads to enterocyte apoptosis (11).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, molecules known to be involved in immune reactions, such as high mobility group box protein 1 (HMGB1), have been detected within apoptotic microparticles (Pisetsky, 2014;Schiller et al, 2013;Spencer et al, 2014). Defects in clearance of apoptotic material are considered a major pathogenetic factor in the development of SLE, and high levels of circulating apoptotic material have been found in many patients.…”
Section: Introductionmentioning
confidence: 99%
“…8C). Recently, it was shown by Shiller et al [67] that High mobility group box protein B1 (HMGB1), a nuclear protein reportedly involved in structural organization of DNA and usually released from the necrotic cells or upon cellular activation, is translocated into the ACMV at apoptosis , also in paper in press, further supporting a proposed hypothesis.…”
Section: Fig 8 a -Apoptotic (Uv-b Irradiated) Hela Cells Produce Bimentioning
confidence: 56%